The flavivirus envelope protein E: isolation of a soluble form from tick-borne encephalitis virus and its crystallization. - Heinz, F X (1991)
By the use of limited trypsin digestion of purified virions, we generated a membrane anchor-free and crystallizable form of the tick-borne encephalitis virus envelope glycoprotein E. It retained its reactivity with a panel of monoclonal antibodies, and only subtle structural differences from the native protein E were recognized. Treatment with the bifunctional cross-linker dimethylsuberimidate resulted in the formation of a dimer. Crystallization experiments yielded hexagonal rod-shaped crystals suitable for X-ray diffraction analysis.